Implementation of hyperthermia management with warm compress technique in fever convulsive children: A case study - Setiawati, Shella; Ferdi, Roni; Jian, Lim Wei (Indonesian Journal of Health Services, 2024)
Background: Hyperthermia in children with febrile seizures represents a critical clinical condition that requires prompt and appropriate management to prevent complications. Pediatric thermoregulation remains physiologically immature, which increases vulnerability to temperature instability and neurological disturbances during fever episodes. Effective nursing interventions are therefore essential for controlling body temperature in pediatric patients experiencing febrile seizures. Objective: This study aimed to explore the implementation of hyperthermia management using warm compress techniques in children with febrile convulsions through a case study approach. Methods: This study employed a descriptive case study design involving two pediatric patients aged 6 months to 5 years who experienced febrile seizures. The study was conducted in the working area of UPTD Tanjung Baru in June 2022. Data were collected through nursing assessment, observation, interviews with caregivers, and documentation review. The intervention consisted of hyperthermia management using warm compress techniques combined with nursing observation and caregiver education. Results: The initial assessment indicated that both patients experienced severe hyperthermia with body temperatures above 40°C. Following the implementation of warm compress interventions, body temperatures decreased to normal ranges, reaching 36.5°C in Patient A and 36.0°C in Patient R. Clinical evaluation demonstrated improved physiological stability and caregiver-reported improvement in the children’s conditions. Conclusion: Warm compress techniques represent an effective non-pharmacological nursing intervention for reducing hyperthermia in children with febrile seizures. The implementation of structured nursing care and caregiver education contributes to improved pediatric fever management in primary healthcare settings.